(untitled) (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2015)
In recent years, we have witnessed a continuous increase in the number of embedded devices with communication capabilities that are changing the way we live, work and play.Â Smart grids, remote monitoring and control of all kinds of consumer devices and industrial equipment, vehicular telematics and e-health devices, are some examples of this revolution.Â The communication between those devices (Machine-to-Machine communication) is leading to a complexity explosion and a strongly fragmented market. The goal of our work is to design an architecture for a generic communication system enabling many kinds of services and devices to function together in a distributed M2M ecosystem regardless of the application domain. This paper presents an initial communication architecture design for an interoperable Machine-to-Machine (M2M) system. The architecture of the system itself is divided into three main components: gateways, distributed servers and communication overlay. Gateways are designed to enable interoperability with various external systems that are, for some reason, unable to directly become parts of the M2M overlay. Servers are required to act as central points for relaying messages, providing authorization, enforcing security policies such as channel encryption and so on. Multiple intercommunicating servers, or server federation, is supported and considered an essential part of the interoperable M2M system. The overlay component refers to the logical M2M network, which is built on top of the existing ICT infrastructure.Â